The Role of Training and Mentoring on Entrepreneurial Behavior Through the Entrepreneurial Intention Approach (A Case Study of the Vocational Training Center in Tasikmalaya Regency) - Fadila, Aldia; Nandang, Nandang; Rachmani , Nizza Nadya (The Future of Education Journal, 2025)
Training and mentoring play an important role in shaping entrepreneurial behavior. This study aims to describe training, mentoring, entrepreneurial intention, and entrepreneurial behavior to determine the extent to which training and the impact of mentoring through entrepreneurial intention affect entrepreneurial behavior among alumni of training participants at the Vocational Training Center (BLK) in Tasikmalaya Regency. The research method used is quantitative with a descriptive approach and path analysis. The population in this study consists of 88 participants, with the same number of 88 samples selected through Saturated Sampling. Data collection was carried out using a questionnaire in the form of a Google form, and the analysis was conducted using Structural Equation Modeling (SEM).